FERTILIZATION STRATEGY TO INCREASE RICE GROWTH AND PRODUCTION UNDER TWO FLOODING CONDITION ON TWO LOWLAND SWAMP TYPES - Gribaldi Gribaldi; Rujito A. Suwignyo; Merry Hasmeda; Renita Hayati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
Flood is general phenomenon found in most areas of Indonesia. This can obstruct rice crop cultivation on lowland swamp areas. Fertilization strategy is one of the efforts to increase rice crop growth and production on flooded condition. The objective of this research was to determine the best fertilization strategy on vegetative stage related to rice crop growth and production under flooded condition at two types of lowland swamp. The experimental design used in this research was split-plot design with three replications. The main plot was fertilization treatment consisting of P1 = base fertilization, P2 = fertilization before flooded, P3 = fertilization after flooded and P4 = fertilization before and after flooded. The subplot was rice variety which consisted of V1 = Inpara 3, V2 = Inpara 5, V3 = IR 64 and V4 = Ciherang. The results showed that fertilization strategy was capable of increasing rice crop growth and production under flooded condition at two types of lowland swamp. Rice variety Inpara 5 added with fertilizer before flooded on shallow-backswamp and fertilizer addition before and after flooded on middle-backswamp was the best treatment that had produced rice yield with magnitude of 4.48 and 3.43 ton per hectare, respectively.